An exploration into the visual aspects of roadmaps: the views from a panel of experts. (2017) - Kerr, Clive; Phaal, Robert
Roadmapping is an established and popular method for strategic planning. Its strength is often characterised in terms of the visual way in which it can embody future plans and present pathways to realising an organisation's vision. However, although a roadmap is a visual management tool, the visual aspects from a graphic design perspective have been largely overlooked. In order to explore this perspective, a panel of experts was brought together for a research workshop which consisted of a focus group activity and a visual critique. The focus group elicited the good vs. bad visual features of roadmap visualisations. This was followed by a critique exercise where a sample set of representative roadmaps were examined in terms of their structural layout, graphical objects and population with content. These roadmaps were also empirically assessed (scored and ranked) to give an indication of their 'visual design goodness'.